Lmx1b activation in axolotl limb regeneration. Issue 9 (23rd April 2022) - Yamamoto, Sakiya; Kashimoto, Rena; Furukawa, Saya; Ohashi, Ayaka; Satoh, Akira
Abstract: Background: Axolotls can regenerate their limbs. In their limb regeneration process, developmental genes are re‐expressed and reorganize the developmental axes, in which the position‐specific genes are properly re‐expressed. However, how such position specificity is reorganized in the regeneration processes has not been clarified. To address this issue, we focused on the reactivation process of Lmx1b, which determines the limb dorsal identity in many animals. Results: Here, we show that Lmx1b expression is maintained in the dorsal skin before amputation and is activated after amputation. Furthermore, we demonstrate that only cells located in the dorsal side prior to limb amputation could reactivate Lmx1b after limb amputation. We also found that Lmx1b activation was achieved by nerve presence. The nerve factors, BMP2+FGF2+FGF8 (B2FF), consistently reactivate Lmx1b when applied to the dorsal skin. Conclusions: These results imply that the retained Lmx1b expression in the intact skin plays a role in positional memory, which instruct cells about the spatial positioning before amputation. This memory is reactivated by nerves or nerve factors that can trigger the entire limb regeneration process. Our findings highlight the role of nerves in amphibian limb regeneration, including both the initiation of limb regeneration and the reactivation of position‐specific gene expression. Key Findings: The mechanism of cell spatial recognition in limb regeneration is unknown. We investigated the activation process of Lmx1b, which is important to establish dorsal identity. Lmx1b is activated only in cells that were located in the dorsal region before amputation. Lmx1b is activated by nerves or by the nerve factors, BMP2+FGF2+FGF8. We suggest that the positional memory of the cells is maintained as faint expressions of position‐specific genes and that the nerve factors are required for its activation.